1998
DOI: 10.1017/s0022149x00000924
|View full text |Cite
|
Sign up to set email alerts
|

Dung-derived biological agents associated with reduced numbers of infective larvae of equine strongyles in faecal cultures

Abstract: Two sets of dung-derived organisms from soil routinely fertilized with manure (MA) and soil chemically fertilized (CH) were cultured separately in the laboratory. Baermannized organisms from these cultures were added to 20 g of faeces from strongyle-infected horses to form three treatment groups: (i) no soil organisms; (ii) low inoculum of soil organisms containing all organisms present in a suspension of approximately 100 adult female free-living nematodes; and (iii) high inoculum containing those soil organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that deposited fresh faeces are quickly colonised by various species of these fungi (Hay et al, 1997;Bird et al, 1998). It has also been found that the fungi are picked up by grazing livestock (cattle, sheep and horses) and subsequently excreted in the voided faeces (Larsen et al, 1994;Manueli et al, 1999).…”
Section: Biological Controlmentioning
confidence: 99%
“…Recent studies have shown that deposited fresh faeces are quickly colonised by various species of these fungi (Hay et al, 1997;Bird et al, 1998). It has also been found that the fungi are picked up by grazing livestock (cattle, sheep and horses) and subsequently excreted in the voided faeces (Larsen et al, 1994;Manueli et al, 1999).…”
Section: Biological Controlmentioning
confidence: 99%